THE ROLE OF THE WORK “MAKTUBAT” IN THE NAQSHBANDI-MUJADDIDI ORDER (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The article reveals the role of “Maktubat” in the formation of the Naqshbandi-Mujaddidi order and its current significance. Also states in this article “Maktubat” served as a program in the formation of the Naqshbandi-Mujaddidi order. The work embodies the theoretical foundations of the Naqshbandi-Mujaddidi order. It is revealed that the issues of wahdatu al-wujud and other controversies in the teachings of Sufism are explained in a clear way.